Phylogenetic Variation of Chelonid Alphaherpesvirus 5 (ChHV5) in Populations of Green Turtles Chelonia mydas along the Queensland Coast, Australia. Issue 3 (19th May 2017) - Ariel, E.; Nainu, F.; Jones, K.; Juntunen, K.; Bell, I.; Gaston, J.; Scott, J.; Trocini, S.; Burgess, G. W.
Abstract: Sea turtle fibropapillomatosis (FP) is a disease marked by the proliferation of benign but debilitating cutaneous and occasional visceral tumors, likely to be caused by chelonid alphaherpesvirus 5 (ChHV5). This study presents a phylogeny of ChHV5 strains found on the east coast of Queensland, Australia, and a validation for previously unused primers. Two different primer sets (gB‐1534 and gB‐813) were designed to target a region including part of the UL27 glycoprotein B (gB) gene and part of UL28 of ChHV5. Sequences obtained from FP tumors found on juvenile green turtles Chelonia mydas (<65 cm curved carapace length) had substantial homology with published ChHV5 sequences, while a skin biopsy from a turtle without FP failed to react in the PCRs used in this study. The resulting sequences were used to generate a neighbor‐joining tree from which three clusters of ChHV5 from Australian waters were identified: north Australian, north Queensland, and Queensland clusters. The clusters reflect the collection sites on the east coast of Queensland with a definitive north–south trend. Received October 22, 2016; accepted May 7, 2017 Published online July 26, 2017